Immersive heritage through Gaussian Splatting: a new visual aesthetic for reality capture - Jamil, Osama; Brennan, AnnMarie (Frontiers in Computer Science, 2025)
This paper investigates the emerging use of 3D generative artificial intelligence (GenAI) models, particularly Gaussian Splatting (GS), for creating immersive virtual environments in architectural heritage contexts. While traditional methods like photogrammetry have long been used to replicate historical sites, advances in AI-driven tools such as Neural Radiance Fields (NeRFs) and GS have significantly broadened accessibility and creativity in 3D reality capture. Though both technologies have been explored previously for heritage conservation, their usage has always been discussed through the lens of accuracy and precision. The paper challenges these traditional notions and follows a phenomenological methodology that analyses the visual aesthetics and image-making techniques of GS from theoretical and philosophical standpoints. Through the lens of architectural and media theory, the research assesses how GS can transform historical sites into immersive experiences by combining photorealism with artistic expression. The approach is twofold: first, analyzing the visual features and characteristics of GS by documenting, representing, and experiencing a real-life heritage site (The Gatekeeper’s Cottage) through immersive mediums. The results are captured as video recordings and are examined in the results section of the paper. Secondly, the paper includes an in-depth overview of how digital artists use GS technology to evoke memory and atmosphere in virtual heritage spaces through narrative building, VFX, and post-production. The purpose of the study is to offer architects, historians, and heritage professionals a new aesthetic perspective on employing AI-driven models for heritage visualization and immersive environments, that challenge the traditional notions of accuracy and question how these techniques can reveal previously hidden or unobservable architectural features in immersive heritage environments.